2020
DOI: 10.1371/journal.pone.0228912
|View full text |Cite
|
Sign up to set email alerts
|

Valuing invisible catches: Estimating the global contribution by women to small-scale marine capture fisheries production

Abstract: The role that women play in fisheries around the world is receiving increasing international attention yet the contributions by women to fisheries catches continues to be overlooked by society, industry and policy makers. Here, we address this lack of visibility with a global estimation of small-scale fisheries catches by women. Our estimates reveal that women participate in small-scale fishing activities in all regions of the world, with approximately 2.1 million (± 86,000) women accounting for roughly 11% (±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 55 publications
2
66
1
10
Order By: Relevance
“…These studies confirmed that women significantly played their economic role through accessing ICTs, microfinancing, tourism development, reproductive healthcare decisions, and business entrepreneurship activities. Secondly, the more significant number of earlier literature focuses on women's role in improving the global environment [18][19][20][21][22][23]. These studies argued that women's role in improving the global environment is merely possible when they fully acquired political autonomy, technology skills, reproductive healthcare treatments, organic agriculture production, energy value chain, financial literacy, and environmental awareness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies confirmed that women significantly played their economic role through accessing ICTs, microfinancing, tourism development, reproductive healthcare decisions, and business entrepreneurship activities. Secondly, the more significant number of earlier literature focuses on women's role in improving the global environment [18][19][20][21][22][23]. These studies argued that women's role in improving the global environment is merely possible when they fully acquired political autonomy, technology skills, reproductive healthcare treatments, organic agriculture production, energy value chain, financial literacy, and environmental awareness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In any case, with estimates identifying more than 2.1 million women participating in small scale fishing activities [4], quantifying the role of women in fisheries is an important aspect, not only from a social but also from an economic, labour and ecological point of view [5 , 10].Thus, there is an urgent need for empowerment of women to act on their own behalf to achieve a greater control over their lives and destinies. The process of…”
Section: Resultsmentioning
confidence: 99%
“…There is an overarching lack of transparency and accountability in subsidy programs, which are rarely based on long-term goals for coastal regions or incentives for sound management [21]. Subsidies are usually granted to vessel or license owners, who are not always fishers and are mostly men, worsening gender inequities [22] (SDG 5.a).…”
Section: Harmful Subsidies Undermine the Sdgs: Why A Global Agreementmentioning
confidence: 99%